IMPLEMENTASI SCIENTIFIC APPROACH DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN IMPLIKASINYA TERHADAP BUDI PEKERTI SISWA DI SMP NEGERI 4 REJANG LEBONG - Alfiyanti Alfiyanti (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2019)
The implementation of PAI learning uses a scientific approach in Rejang Lebong State Middle School with prosudur as expected by the curriculum 13. Students under the guidance of two PAI teachers observe student learning activities in responding to the lessons given by the teacher as well as asking questions, exploring to the field as well as short film observations given by the teacher to find concrete examples of how to empathize with others describe and analyze conclusions about the importance of empathy for others and devotion to parents and teachers. PAI learning with a scientific approach, especially in the material of students ‘character in Rejang Lebong 4 Public Middle School, has good implications for forming students’ morals for the better. This is because students are required to practice directly the phenomena that arise from existing learning material. Experiments carried out through observation and simple reports and then discussed in class groups are effective approaches so that they understand, remember and practice the messages in the material, so that they respect the opinions of others, sensitive to the calamities that befall other people, especially to the two parents and teachers and behave in accordance with religious norms and customs.